SOSIALISASI TERHADAP MASYARAKAT PENERIMA BANTUAN PKH SEBAGAI MASYARAKAT SADAR BANSOS MENUJU MASYARAKAT SEJAHTERA DI SUMBERTAMAN KOTA PROBOLINGGO - Nuril Hidayati; Tri Prihatiningsih; Mimik Umi Zuhroh; Indah Puspa Sari (Bajang Institute, 2025)
Social assistance (bansos) is an important instrument in overcoming poverty and improving community welfare. However, the success of social assistance really depends on the level of public awareness of its management and use. This service program aims to increase community awareness and participation in managing social assistance through education, training and multi-sector collaboration. This activity involves various elements of society, local government and NGOs to create a social assistance system that is more transparent, targeted and sustainable. The results of this program show an increase in people's understanding of social assistance and strengthening their capacity to use assistance productively, towards a more prosperous society. PKH social assistance as one of the social assistance received by the people of Sumbertaman, Probolinggo city is a form of community awareness of social assistance towards a prosperous society and not making them dependent on aid and becoming an economically independent society.